Working in the Offshore Petroleum Industry - House, J. Douglas (John Douglas) (The Challenge of Oil: Newfoundland's Quest for Controlled Development, 1998)
...This chapter about working in the offshore petroleum industry will examine the nature and conditions of the work, industrial relations and offshore safety. Since the industry is truly international, and since evidence on the offshore workplace is hard to come by (because of the industry's reluctance to release such data), I will draw upon the fragment evidence available from other parts of the world as well as from Newfoundland. –From author's introduction
Keywords: Offshore oil industry – Government policy – Canada